Earthquake waves and the mechanical properties of the earth's interior (1967)
It has come to be realized in the present century that the science of Seismology, in addition to providing information on the nature and characteristics of earthquakes, is a central source of knowledge of the mechanics and layering of the Earth's deep interior.